The Effects of Dancing at Young People with “Down’s Syndrome” - Raluca Crisan (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
Dance and movement therapy is about the creative use of movement and dancing in a therapeutic alliance. The present study analysis semi-structured interviews from people connected to young people with Down’s syndrome. Our subjects practiced dances like ballet, Zumba, vals, tango, and also therapeutic movement. Some of them proved their skills in events specially organized for people with disabilities, but also in inclusive events, where they danced together with professional dancers, in Romania, the Republic of Moldavia, and Italy. The effects of dancing include increased self-esteem, relaxation, social inclusion, improved learning skills; they also developed social skills, because they met a lot of people in different societies contexts.